The Role of Insurance in the Risk Management Concepts of Contemporary Enterprises - Bednarczyk, Teresa H.; Szymańska, Anna (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis: Theoretical concepts to risk management in the enterprises evolve over time due to the rapid changes taking place both in the external and internal environment. The traditional approach to risk management gradually gives way to new concepts of the philosophy of holistic enterprise risk management. The aim of the study is to analyze these two concepts in terms of determining the current role and practical significance of the insurance method. The study verified the following research hypothesis: Despite the changing theoretical concepts of risk management, as well as the relative increase in the significance of uninsurable risk, in practice the insurance method still remains an important tool, especially in the risk management of large and medium-sized enterprises. Methodology: The study is a theoretical and empirical in nature. The theoretical part was based on studies of domestic and foreign literature. The empirical part was based on a survey of the selected empirical studies and reports from advisory and consulting institutions, including the latest AON Polska 2019 report on risk management in enterprises Results of the research: Most domestic enterprises implement a silo risk management model, and insurance as a method of financing the effects of risk materialization is still not losing its importance. Although the relative importance of insurance is decreasing due to the growing importance of uninsurable risk, such as the risk of economic and geopolitical instability, economic slowdown, increasing competition or lack of professional personnel, insurance has not lost its key role in practice, especially in large and medium-sized enterprises.